Spectrum effect correlation of yangyin tongnao granules on cerebral ischemia-reperfusion injury rats - Zhang, Yangyang; Yu, Li; Yang, Jiehong; Ding, Zhishan; He, Yu; Wan, Haitong (Frontiers in Pharmacology, 2022)
Yangyin Tongnao Granules (YYTNG), as a traditional Chinese medicine (TCM) compound preparation, have a good curative effect on cerebral ischemia-reperfusion injury. This study was to investigate the relationship between the active components of YYTNG in plasma and the inflammatory response in cerebral ischemia-reperfusion injury rats. High performance liquid chromatography (HPLC) was performed to determine the fingerprints at different time points of middle cerebral artery occlusion (MCAO) rats after administration of YYTNG at different time. Enzyme-linked immunosorbent assay (ELISA) was used to detect the levels of interleukin-18 (IL-18) and tumor necrosis factor-α (TNF-α) in the plasma of MCAO rats at different time points. The spectral-effect relationship between YYTNG fingerprints and inflammatory indexes in vivo was established by combining three mathematical models, grey correlation, multiple linear regression and partial least-square method. The results showed that each chromatographic peak in the HPLC of plasma had a certain correlation with the inflammatory index, and the order was: P2>P6>P5>P1>P3>P4. Therefore, this study successfully established the spectrum effect correlation of YYTNG on cerebral ischemia-reperfusion injury rats. It provides a certain guiding ideology for the analyses of the relationship between fingerprints and pharmacodynamics of TCM prescriptions.